Pierrot Requiem : Journey in Socio-Cultural Issues. - Ichikawa, Tadao (World Scientific Publishing Company, 2002)
This book is a collection of true-to-life essays which offers the reader various ways to view the socio-cultural state of the modern world as seen through the eyes of the author - a somewhat cynical but ethical Japanese professor. Through journeys in various cultures, these stories break numerous stereotypes, from the failure of higher education in Japan to the mysteries of using various types of toilets in Mediterranean Europe. The author narrates brief encounters with all aspects of society, from radical students to conservative academicians, from old-style street merchants to modern busines.